A Mediation Analysis of Mothers' Dietary Intake: The Entre Familia: Reflejos de Salud Randomized Controlled Trial. (August 2018) - Horton, Lucy A.; Ayala, Guadalupe X.; Slymen, Donald J.; Ibarra, Leticia; Hernandez, Erika; Parada, Humberto; Rock, Cheryl L.; Arredondo, Elva M.; Elder, John P.
Aims . Examine intervention effects among mothers involved in a healthy eating randomized controlled trial. Furthermore, examine the mediating roles of individual and familial influences on observed outcomes. Methods . Between 2009 and 2011, 361 families were recruited; half were assigned to an 11-session community health worker–delivered family-based intervention targeting Spanish-speaking Latino families in Imperial County, California. The intervention was delivered over a 4-month period. Home visits and telephone calls were delivered approximately weekly, with tapering near the end of the intervention to promote independence from the promotora . In this article, mothers' self-reported dietary intake was the primary outcome. Evaluation measures were taken at baseline, 4 months, and 10 months. Results . Daily servings of fruits were higher among intervention versus control mothers (mean = 1.86 vs. mean = 1.47; effect size [ES] = 0.22) at 10 months post-baseline. Mothers in the intervention versus control condition also reported consuming a lower percent energy from fat (mean = 30.0% vs. 31.0%; ES = 0.30) and a higher diet quality (mean = 2.93 vs. mean = 2.67; ES = 0.29). Mediators of improvements were behavioral strategies to increase fiber and lower fat intake, family support for vegetable purchasing, and decreased unhealthy eating behaviors and perceived family barriers to healthy eating. Discussion and Conclusion . Family-based behavioral interventions are effective for changing the skills and family system needed to improve diet among Latina mothers. Health care providers and other practitioners are encouraged to target skill development and fostering a socially supportive environment.